Bacteriophage T7 gene 2.5 protein: an essential protein for DNA replication. - Kim, Y T (1993)
The product of gene 2.5 of bacteriophage T7, a single-stranded DNA binding protein, physically interacts with the phage-encoded gene 5 protein (DNA polymerase) and gene 4 proteins (helicase and primase) and stimulates their activities. Genetic analysis of T7 phage defective in gene 2.5 shows that the gene 2.5 protein is essential for T7 DNA replication and growth. T7 phages that contain null mutants of gene 2.5 were constructed by homologous recombination. These gene 2.5 null mutants contain either a deletion of gene 2.5 (T7 delta 2.5) or an insertion into gene 2.5 and cannot grow in Escherichia coli (efficiency of plating, < 10(-8)). After infection of E. coli with T7 delta 2.5, host DNA synthesis is shut off, and phage DNA synthesis is reduced to < 1% of phage DNA synthesis in wild-type T7-infected E. coli cells as measured by incorporation of [3H]thymidine. In contrast, RNA synthesis is essentially normal in T7 delta 2.5-infected cells. The defects in growth and DNA replication are overcome by wild-type gene 2.5 protein expressed from a plasmid harboring the T7 gene 2.5.